Fields of Gold : Financing the Global Land Rush - Fairbairn, Madeleine (Book collections on Project MUSE., 2020)
"Over the last decade, the financial sector has suddenly begun investing in farms; Fields of Gold critically examines the history, ideas, and political struggles surrounding this "financialization of farmland"--